Prevalence and Pattern of Internet Addiction among Adolescents in a Holiday Camp in Nigeria Post-COVID-19 Pandemic - Chioma N. Mbachu; Ifeoma B. Udigwe; Emeka Okoh; Ikechukwu I. Mbachu; Stanley K. Onah; Chizalu I. Ndukwu; Uche M. Umeh; Chioma Clive-Opara; Joy C. Ebenebe; Richard Uwakwe (International Journal of Medicine and Health Development)
Background: Internet addiction (IA) is a global public health problem that significantly impacts adolescents’ well-being, with a notable increase in the rate of Internet use during the coronavirus disease 2019 (COVID-19) period. However, few studies have explored the rate and pattern of IA in a holiday camp, which provides an inclusive haven for adolescents from diverse backgrounds to interact together. Objective: To determine the prevalence and pattern of IA among adolescents in a holiday camp in Nigeria post-COVID-19 pandemic. Materials and Methods: Data on the demographic profile and the Internet addiction test (IAT) were collected using an IAT questionnaire, and analysis was conducted using STATA 16.0 with a significance level set at P < 0.05. Results: Of the 243 participants, 136 had IA, resulting in an IA prevalence of 56.0%; 71/243 (29.2%) had mild IA, 62/243 (25.5%) had moderate IA, and 3/243 (1.2%) had severe IA. The IA rate was higher among late adolescents (80.0%) compared to early (35.0%) and middle adolescents (55.0%) (p = 0.009). On logistic regression, late adolescence (odds ratio (OR) = 2.71; 95 CI 1.39–5.27), male sex (OR = 2.67; 95 CI 1.36–5.24), and spending more than 3 h online daily (OR = 13.67; 95 CI 6.24–29.91) were associated with increased risk of IA. Conclusion: As a result of the COVID-19 pandemic, there is a significant prevalence of IA among adolescents in a holiday camp in Nigeria, impacting 56% of the population. This addiction is strongly linked with late adolescence, male sex, and spending more than 3 h online each day.